2018
DOI: 10.14742/ajet.3557
|View full text |Cite
|
Sign up to set email alerts
|

“You have to teach to your personality”: Caring, sharing and teaching with technology

Abstract: Studies of teachers in higher education have acknowledged the relationship between teaching and teacher identity. Teacher identity is seen as dynamic, context-specific, and encompassing a teachers' sense of meaning, values and self-esteem. This article considers the relationship between the values dimension of teacher identity and the use of technology. Using qualitative data from a multisite case study, it explores three aspects of the relationship between values and technology in teaching: firstly, the exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A positive attitude of a teacher will have a positive influence on students in particular and society in general (Chan & Yuen, 2014). The teaching and learning process is the core of the overall educational process, with the teacher as the main role player (Chiva-Bartoll, 2018;Shelton, 2018). The abilities and characteristics needed to be a good teacher are the same factors that determine a good education (Djigić et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A positive attitude of a teacher will have a positive influence on students in particular and society in general (Chan & Yuen, 2014). The teaching and learning process is the core of the overall educational process, with the teacher as the main role player (Chiva-Bartoll, 2018;Shelton, 2018). The abilities and characteristics needed to be a good teacher are the same factors that determine a good education (Djigić et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…presenting their commitments to learners, expressing care to learners' needs; sharing their value-laden personality, etc. ; Shelton, 2018). Developing a Community of Practice (9.09%).…”
Section: Results To Affordances For L2 Teacher Identity Developmentmentioning
confidence: 99%
“…Engaging with Social Media Could Challenge Teacher's Self-image (15.91%). Exploring the impact of using technology on teacher identity development, Shelton (2018) reported that teachers would have a negative impression if they perceive technology as a constraining factor of their personal agency. As a solution, the use of media needs to be integrated into distance learning by enhancing teachers' digital literacy in terms of self-presentation and establishing personal boundaries.…”
Section: Results To Challenges For L2 Teacher Identity Developmentmentioning
confidence: 99%
“…Poor digital literacy on the part of preservice teachers can result in a negative self‐image (Vella, 2013). Shelton (2018) reported that some preservice teachers considered educational technology as a constraining factor rather than a facilitative factor, thereby negatively affecting their personal agency. The argument is that predetermined instructional designs in educational technology cause managerial coercion and, as a result, loss of professional autonomy that negatively impacts professional self‐image (D. R. Johnson, 2012; Veletsianos & Kimmons, 2013).…”
Section: Resultsmentioning
confidence: 99%